Analisis Visual dan Filosofi Patung Kuda Berkepala Manusia pada Tradisi Tabuik Pariaman - Gunawan, Nando; Pebriyeni, Eliya (TSAQOFAH, 2025)
This study is grounded in the importance of understanding symbolism in cultural traditions as an expression of the philosophical values of local communities. It examines the visual form and embedded philosophical meanings of the horse statue with a human head, a central element in the Tabuik celebration in Pariaman, West Sumatra. Tabuik is an annual ritual of the Pariaman community commemorating the Day of Ashura in the Shi’a Islamic tradition, honoring the events of Karbala and the sacrifice of Imam Husayn. The tradition reflects a fusion of religious elements and local culture rich in symbolism. This research adopts a descriptive qualitative method with Roland Barthes’ visual semiotics approach, analyzing meaning on three levels: denotative (literal), connotative (cultural associations), and myth (ideological and philosophical values). The findings reveal that the statue represents a synergy between local beliefs and Islamic history, particularly the narrative of Karbala and the journey of Buraq. The female face on the statue's head symbolizes gentleness and motherhood, representing Bundo Kanduang as an emblem of honor in Minangkabau culture. The concept of a “level journey” conveys the philosophical view that all humans are equal and share a common purpose toward goodness. The study concludes that the horse statue with a human head serves as a visual medium that represents the cultural identity, religious beliefs, and life philosophy of the Pariaman community.